2017
DOI: 10.1017/s1742170517000357
|View full text |Cite
|
Sign up to set email alerts
|

Organic farmer perceptions of reduced tillage: A Michigan farmer survey

Abstract: A common critique of organic farming is that it is very tillage intensive, and therefore deleterious to soil quality. However, little information is available on the tillage practices currently employed by organic farmers, as well as organic farmers’ attitudes toward reduced tillage (RT). To address these knowledge gaps, a detailed written survey of Michigan organic field crop and vegetable farmers was conducted to investigate their current tillage practices, as well as their perceptions of the barriers and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…While 53% of respondents did not report using cover crops, an overwhelming majority of those farmers (78%) reported growing some type of perennial crop during the four-year crop rotation. An overwhelming majority of respondents (92%) also implemented tillage at least once during the fouryear rotation, which is unsurprising since organic farmers typically rely on tillage to control weeds (Lowry & Brainard, 2017).…”
Section: Farm Demographics and Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…While 53% of respondents did not report using cover crops, an overwhelming majority of those farmers (78%) reported growing some type of perennial crop during the four-year crop rotation. An overwhelming majority of respondents (92%) also implemented tillage at least once during the fouryear rotation, which is unsurprising since organic farmers typically rely on tillage to control weeds (Lowry & Brainard, 2017).…”
Section: Farm Demographics and Management Practicesmentioning
confidence: 99%
“…Given that this dataset consists of farms that have implemented a wide range of management practices over a four-year period, these analyses needed to go beyond analysis of variance to fully explore the relationships amongst the various management practices in addition to the relationship between management practices and individual soil health indicators. For instance, a consistent critique of organic agriculture is that it heavily relies on tillage intensity for weed control, which has the potential to reduce soil health (Bhardwaj et al, 2011;Lowry & Brainard, 2017;Osterholz et al, 2020). Thus, we were particularly interested in understanding the relationship between tillage frequency and crop diversity in addition to tillage frequency and use of perennials (Figure 4).…”
Section: Management Complexity In Organic Farming Systemsmentioning
confidence: 99%
“…Preventive and cultural weed management strategies that act to decrease weed emergence and increase crop competitiveness must be integrated into organic systems for reduced tillage to be a viable option (Barberi 2002; Brainard et al 2013; Mirsky et al 2013). Surveys of organic growers in Michigan demonstrate that they are well aware of soil-related benefits of reducing tillage but are hesitant to adopt reduced-tillage practices, in large part due to concerns that weed management will become a greater challenge (Lowry and Brainard 2017a). Two cultural strategies that may increase crop competitiveness and reduce weed management costs are use of cover crop mulches and targeted placement of nutrient amendments.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has demonstrated that no‐till increases soil organic matter and carbon sequestration—a major benefit in a time of growing concern over industrial agriculture’s contribution to the release of greenhouse gases (Lal 2004; Bayer et al 2006; Baker et al 2007). Several studies also highlight that no‐till and reduced tillage have gained acceptance among farmers because of perceived reductions in operating costs—including lower fuel and labor expenses—in addition to the aforementioned environmental benefits (Sattler and Nagle 2010; Vitale et al 2011; Lowry and Brainard 2019; Bavorová et al 2020).…”
Section: Introductionmentioning
confidence: 99%